2023
DOI: 10.3389/fphar.2023.1004465
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Omega-3 polyunsaturated fatty acids in adjuvant treatments for colorectal cancer: A meta-analysis of randomized controlled trials

Abstract: Background: Colorectal cancer (CRC) ranks third globally. There are many adverse reactions to treatments such as surgeries and post-surgical chemotherapy, which affect patients’ prognosis and reduce their life quality. Omega-3 polyunsaturated fatty acids (O3FAs) have become an essential part of immune nutrition due to their anti-inflammatory properties, which improve body immunity and have attracted widespread attention. A systematic review focused on the efficacy and safety of O3FAs for patients undergoing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Recent studies have also shown that EPA can significantly reduce the levels of serum TNF- α and IL-6 in tumor patients. At the same time, EPA can reduce the level of inflammatory reaction and improve body immune function by reducing the production of C-reactive protein and limiting the release of IL-6 ( Liu et al, 2023 ). It is suggested that the expression levels of EPA and post SCC-Ag may be auxiliary markers for monitoring disease progression and tumor malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that EPA can significantly reduce the levels of serum TNF- α and IL-6 in tumor patients. At the same time, EPA can reduce the level of inflammatory reaction and improve body immune function by reducing the production of C-reactive protein and limiting the release of IL-6 ( Liu et al, 2023 ). It is suggested that the expression levels of EPA and post SCC-Ag may be auxiliary markers for monitoring disease progression and tumor malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…20 In this regard, a study indicated that omega-3 PUFAs were safe and effective in lowering TNF-α and IL-6 levels and shortening the length of hospital stay for patients with CRC undergoing adjuvant therapies. 83 An anticancer effect of EPA and DHA was reported through a reduction in the proliferation, metastasis, and inflammation of cancer cells. 27 CRC may be suppressed by some other dietary components such as probiotics, prebiotics, and synbiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests that nutrition may improve muscle mass (61), short-chain fatty acids (SCFAs) in particular, which are considered to be involved in the change of muscle biology (62). On the other hand, immune nutrition with some special nutrients has been widely used in patients with cancers, showing different supporting functions (63,64). Therefore, adding nutrients like SCFAs to the formula of nutrition may help to treat both diseases.…”
Section: Figurementioning
confidence: 99%